Stable Isotope Characteristics of Akiri Vein Copper Mineralization, Nasarawa, Nigeria - IO Folorunso; RB Bale; JID Adekeye (Journal of Applied Sciences and Environmental Management)
The Akiri vein copper mineralization was investigated for its carbon and oxygen isotopic composition to determine the characteristics of the mineralizing fluid. Carbon and oxygen isotope analyses of Akiri siderite range between δ13C values (-1.05 to -1.71‰) and δ13O values (-14.94 to -15.18) respectively. δ 13C isotopic composition is comparable to values expected for Cretaceous marine carbonates. The 18O depletion in the vein siderite indicates dominant meteoric water sources involved for carbonates precipitation. This significant depletion between the δ18O compositions of Akiri siderite compared with carbonates from other parts of the basin probably indicate differential formational temperature or fluid composition.